2015
DOI: 10.1589/jpts.27.3207
|View full text |Cite
|
Sign up to set email alerts
|

Deep cervical flexor training with a pressure biofeedback unit is an effective method for maintaining neck mobility and muscular endurance in college students with forward head posture

Abstract: [Purpose] This study investigated the effects of deep cervical flexor training on maintaining forward head posture, muscular endurance, and cervical mobility. It also examined the effectiveness of deep cervical flexor training with a pressure biofeedback unit. [Subjects and Methods] Twenty college students were recruited and randomly assigned to groups that underwent either deep cervical flexor training with a pressure biofeedback unit (experimental group, n=10) or conventional deep cervical flexor training (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 15 publications
(39 reference statements)
3
38
0
2
Order By: Relevance
“…Cho18 ) reported that CVA increased meaningfully when applying orthotherapy along with accessory muscle breathing exercises in 18 patients with FHP. Kang19 ) mediated flexion exercises for deep neck flexor muscles using feedback equipment for 10 minutes a day, three times a week, for 6 weeks. As a result, the range of motion and CVA increased.…”
Section: Discussionmentioning
confidence: 99%
“…Cho18 ) reported that CVA increased meaningfully when applying orthotherapy along with accessory muscle breathing exercises in 18 patients with FHP. Kang19 ) mediated flexion exercises for deep neck flexor muscles using feedback equipment for 10 minutes a day, three times a week, for 6 weeks. As a result, the range of motion and CVA increased.…”
Section: Discussionmentioning
confidence: 99%
“…This study used G*Power software version 3.1.7 to calculate the sample size, which was determined based on a one-tailed t-test, power = 0.80, α = 0.05, and effect size = 0.5. In the comparison between the two groups, the effect size of 0.5 was used as the medium [ 23 ]. The required sample size was determined to be 102; thus, 107 participants were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after the application of the soft tissue techniques, four selected neuromuscular retraining exercises were applied to both groups. The rst exercise included the strengthening of the deep neck exors with a combination of neck curl with a chin tuck position in the supine position using the Chattanooga Stabilizer Pressure biofeedback [16]. The second exercise included cervical rotation strengthening through the contraction of the deep exors at the same time as the rotating muscles.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%